Diary of an Illegal Immigrant: Memoirs from Spain and Morocco - Cannon, Elinor B. (Tufts Archival Research Center, 2005)
Immigration in the Europe and North America has become one of the most pressing issues of this century, and the world's civilizations grow closer and closer together every day. In Europe, already a hub for cultural exchange and overlap, people of all social classes and educational backgrounds from North Africa and the Middle East are leaving their countries and transplanting themselves all over the continent. In 1999, Moroccan journalist Rashid Nini published Diario de un illegal (Arabic: Yawm y t muh jir sirr), a compilation of his memoirs and accounts of his time living and working in Spain illegally. The author is an educated, university-graduate Moroccan who arrives to Spain as a "journalist correspondent," but is forced to spend most of his time working in orange fields and cafes. Each chapter is written in the present tense, universalizing each of his experiences and reflecting the thoughts and feelings of all illegal immigrants. Originally written in Arabic, the book has since been translated into Spanish and published in Spain. I have worked to produce an English translation of the book, drawing from both the Arabic and Spanish versions, and used it as a basis for observations on comparative and collaborative translating. Finally, I reflect on the writer's experiences and how they represent the bloc of North African immigrants in Spain as a whole.